2019
DOI: 10.3390/ijms20071681
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia-Induced Downregulation in Expression of nNOS Intramural Neurons of the Small Intestine in the Pig

Abstract: Diabetic autonomic peripheral neuropathy (PN) involves a broad spectrum of organs. One of them is the gastrointestinal (GI) tract. The molecular mechanisms underlying the pathogenesis of digestive complications are not yet fully understood. Digestion is controlled by the central nervous system (CNS) and the enteric nervous system (ENS) within the wall of the GI tract. Enteric neurons exert regulatory effects due to the many biologically active substances secreted and released by enteric nervous system (ENS) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…In this study, we have shown that nNOS occurs in relatively high proportion of enteric neurons, which is in agreement with previous studies, where nitrergic structures have been noted in different mammalian species such as pigs [20,38], guinea pigs [39], mice [39,40] rats [41,42] and humans [43]. The current findings are congruent with the available literature, where more numerous NOS-positive neurons were found in the myenteric plexus [22,44]. Less than 10 % of neurons in both submucous plexuses (outer and inner) were immunoreactive to nNOS, which is similar to previous studies conducted in pigs [22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we have shown that nNOS occurs in relatively high proportion of enteric neurons, which is in agreement with previous studies, where nitrergic structures have been noted in different mammalian species such as pigs [20,38], guinea pigs [39], mice [39,40] rats [41,42] and humans [43]. The current findings are congruent with the available literature, where more numerous NOS-positive neurons were found in the myenteric plexus [22,44]. Less than 10 % of neurons in both submucous plexuses (outer and inner) were immunoreactive to nNOS, which is similar to previous studies conducted in pigs [22].…”
Section: Discussionsupporting
confidence: 93%
“…In turn, the populations of nNOS-expressing nerve cells in both the outer and the inner submucous plexuses were also significantly decreased but to a lesser extent than in the MP. Reduction of nNOS-IR enteric neurons was previously observed during diabetes [44], Chagas' disease [45], Hirschsprung's disease [46], as well as ischemia [22]. In contrast, an increase in the proportions of nNOS-IR enteric intramural neurons was found in the swine small intestine during proliferative enteropathy [47], ileitis [22], inflammatory bowel disease (IBD) [48].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…After a week, diabetes was induced, as previously described [35][36][37]. Streptozotocin (STZ) (Sigma-Aldrich, St Louis, MO, USA, S0130), 150 mg/kg of body weight, was dissolved in a freshly prepared disodium citrate buffer solution (pH = 4.23, 1 g streptozotocin/10 mL solution).…”
Section: Methodsmentioning
confidence: 99%
“…Since diabetes occurs extremely rarely in pigs, exogenous injection of streptozotocin (STZ) is needed to induce diabetes [35]. After a few days of STZ injections, clear symptoms of diabetes are present [36][37][38][39][40][41]. In this experimental model, the main defining factor of diabetes is chronic hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%